SEKOLAH PERJUMPAAN SEBAGAI GERAKAN DAKWAH BERBASIS KOMUNITAS - Putrawan, Agus Dedi (LENTERA, 2018)
Da’wa is on of the most important parts of Islamic teachings. In the context of the implementation of da’wa in the formal school settings, da’wa is responsible for the overall result of the process of implanting Islamic values into school age children. However, da’wa in the settings of formal school is less successful in integrating the objective of da’wa into the learning process and evaluation involving students. This article, thus, aims at revealing the implementation of da’wa within the framework of community school settings in several villages in West Lombok regency. Findings in this article suggest that the implementation of da’wa in the framework of community school settings contributes to the increase in the quality students’ religiousity.Keywords: Community school settings, da’wa, and students’ religiousity.